2015
DOI: 10.1016/j.foodcont.2014.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of bovine milk lactoferrin on the emerging foodborne pathogen Cronobacter sakazakii: Effect of media and heat treatment

Abstract: 11Cronobacter sakazakii is a pathogen transmitted by food, with high osmotic 12 resistance and tolerance to desiccation, which affects mainly to newborns,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 31 publications
1
16
1
Order By: Relevance
“…Poor lactoferrin stability was observed at higher temperatures, as no lactoferrin was detected in milk the treatments at 75 and 85°C. In contrast to our findings, Harouna et al (2015) demonstrated that native lactoferrin is very resistant to most common pasteurisation treatments and can maintain its antibacterial activity against Cronobacter sakazakii (C. sakazakii).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Poor lactoferrin stability was observed at higher temperatures, as no lactoferrin was detected in milk the treatments at 75 and 85°C. In contrast to our findings, Harouna et al (2015) demonstrated that native lactoferrin is very resistant to most common pasteurisation treatments and can maintain its antibacterial activity against Cronobacter sakazakii (C. sakazakii).…”
Section: Resultscontrasting
confidence: 99%
“…In contrast to our findings, Harouna et al . () demonstrated that native lactoferrin is very resistant to most common pasteurisation treatments and can maintain its antibacterial activity against Cronobacter sakazakii ( C. sakazakii ).…”
Section: Resultsmentioning
confidence: 99%
“…As described by Harouna et al (2015), milk samples stored at À20°C were thawed at 4°C and centrifuged at 50009 g for 20 min to remove fat. Twenty milligrams of fat was transferred into a 5-mL tube and esterified with NaOCH 3 : methanol followed by HCl: methanol (Kramer et al 1997).…”
Section: Milk Fatty Acid Analysismentioning
confidence: 99%
“…Therefore, the authors reported that both non-heat-treated and pasteurized lactoferrin showed similar antibacterial properties. Harouna et al (2015) reported that the antibacterial activity of native bovine lactoferrin against Cronobacter sakazakii was retained even with heat treatments at 72℃ for 15 s, 85℃ for 15 s, and 63℃ for 30 min. They also reported that lactoferrin exhibited antibacterial activity after heat treatment at 72℃ for 15 min and 85℃ for 10 min against Cronobacter sakazakii;…”
Section: Resultsmentioning
confidence: 99%